Bioorthogonal click chemistry for fluorescence imaging of choline phospholipids in plants - Paper, Janet M.; Mukherjee, Thiya; Schrick, Kathrin (My University, 2018)
Background: Phospholipids are important structural and signaling molecules in plant membranes. Some fluorescent dyes can stain general lipids of membranes, but labeling and visualization of specific lipid classes have yet to be developed for most components of the membrane. New techniques for visualizing membrane lipids are needed to further delineate their dynamic structural and signaling roles in plant cells. In this study we examined whether propargylcholine, a bioortholog of choline, can be used to label the major membrane lipid, phosphatidylcholine, and other choline phospholipids in plants. We established that propargylcholine is readily taken up by roots, and that its incorporation is not detrimental to plant growth. After plant tissue is harvested and fixed, a click-chemistry reaction covalently links the alkyne group of propargylcholine to a fluorescently-tagged azide, resulting in specific labeling of choline phospholipids. Results:  Uptake of propargylcholine, followed by click chemistry with fluorescein or Alexa Fluor 594 azide was used to visualize choline phospholipids in cells of root, leaf, stem, silique and seed tissues from Arabidopsis thaliana. Colocalization with various subcellular markers indicated coinciding fluorescent signals in cell membranes, such as the tonoplast and the ER. Among different cell types in the leaf epidermis, guard cells displayed strong labeling. Mass spectrometry-based lipidomic analysis of the various plant tissues revealed that incorporation of propargylcholine was strongest in roots with approximately 50% of total choline phospholipids being labeled, but it was also incorporated in the other tissues including seeds. Phospholipid profiling confirmed that, in each tissue analyzed, incorporation of the bioortholog had little impact on the pool of choline plus choline-like phospholipids or other lipid species. Conclusion:  We developed and validated a click-chemistry based method for fluorescence imaging of choline phospholipids using a bioortholog of choline, propargylcholine, in various cell-types and tissues from Arabidopsis. This click-chemistry method provides a direct way to metabolically tag and visualize specific lipid molecules in plant cells. This work paves the way for future studies addressing in situ localization of specific lipids in plants.
Citation: Paper, J. M., Mukherjee, T., & Schrick, K. (2018). Bioorthogonal click chemistry for fluorescence imaging of choline phospholipids in plants. Plant Methods, 14(1). https://doi.org/10.1186/s13007-018-0299-2
Keywords: Phosphatidylcholine; Propargylcholine; Phospholipids; Click chemistry; Arabidopsis thaliana; Fluorescence labeling